2015
DOI: 10.1002/ccd.25983
|View full text |Cite
|
Sign up to set email alerts
|

The use of the acute Pd/Pa drop after intracoronary nitroglycerin infusion to rule out significant FFR: CANICA (Can intracoronary nitroglycerin predict fractional flow reserve without adenosine?) multicenter study

Abstract: The cutoff value of acute Pd/Pa-NTG > 0.88 has a high NPV meaning adenosine-FFR can be avoided in almost half of lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…regadenoson (agonist of adenosine receptor A2A) [25], i.c. sodium nitroprusside [26], nicorandil [27], nitrates [28] and papaverine [17,29]. It is important to note that these substances are much less frequently used and thus, do not often appear in the protocols for large RCTs.…”
Section: Additional Aspects Of Ffr Measurement In Patients Presentingmentioning
confidence: 99%
“…regadenoson (agonist of adenosine receptor A2A) [25], i.c. sodium nitroprusside [26], nicorandil [27], nitrates [28] and papaverine [17,29]. It is important to note that these substances are much less frequently used and thus, do not often appear in the protocols for large RCTs.…”
Section: Additional Aspects Of Ffr Measurement In Patients Presentingmentioning
confidence: 99%
“…From these data, it would appear that a Pd/Pa-NTG>0.88 could be used to defer intervention and that an adenosine-FFR could be avoided in almost half of lesions encountered in routine practice. Unfortunately, based on the author's data scatterplot [2], the ability of Pd/Pa-NTG to identify a lesion with an FFR <0.80 appears weaker, with a Pd/Pa-NTG value of <0.83 required to have high specificity, at the cost of 25% false negatives.…”
mentioning
confidence: 92%
“…In this issue of Catheterization Cardiovascular Interventions, Martin-Reyes et al [2] measured baseline Pd/Pa, Pd/Pa after 0.2 mg intracoronary (IC) nitroglycerin (NTG), and FFR using intravenous adenosine in 283 patients (335 lesions). They found that the optimal cutoff values of resting Pd/Pa and Pd/ Pa-NTG to predict FFR>0.80 were >0.96 and >0.88, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperemic effects of these agents have long been known. Two encouraging studies demonstrated that measurement of the significance of intermediate stenoses was feasible by using contrast medium instead of adenosine [8, 9]. …”
Section: Introductionmentioning
confidence: 99%